The Clinical Relevance of the Thalamogeniculate Arteries in Endoscopic Endonasal Surgery for Giant Pituitary Adenomas in the Interpeduncular Fossa - Pilonieta, Martin; Pérez, Paula; Prevedello, Daniel M. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Bilateral thalamic stroke is usually due to compromised artery of Percheron, an anatomical variation of the vascular supply of the thalamus. The stroke in this area is very uncommon, and is mainly due to top of the basilar syndrome. Other causes are extremely rare. We describe the case of a patient with a pituitary adenoma who underwent surgery and later presented with a bilateral thalamic infarct, suggesting compromise of the artery of Percheron. This would be the third case published in the literature about this complication. We present a literature review about the vascular supply of the thalamus, the artery of Percheron, and its involvement in pituitary surgery.
Keywords: stroke; thalamus; thalamic supply; artery of percheron